Cerebral venous sinus thrombosis with an acute subdural hematoma treated with endovascular intervention: A case report - Crouch, Miranda; Quig, Nathan; Yap, Edward; Lau, Winnie (Frontiers in Neurology, 2022)
We report two cases of endovascular intervention for management of cerebral venous sinus thrombosis complicated by an acute intracranial hemorrhage during treatment with therapeutic anticoagulation. The first patient developed an acute subdural hematoma with progressive enlargement and was subsequently managed with venous sinus thrombectomy. The second patient developed an intraparenchymal and subdural hematoma and was treated with middle meningeal embolization. Anticoagulation is the primary treatment for cerebral venous sinus thrombosis but also contraindicated in an acute intracranial hemorrhage. In these cases, after endovascular intervention both patients resumed therapeutic anticoagulation without further hematoma expansion or additional invasive interventions. Both patients made an excellent neurological recovery and returned to their baseline functional independent status. Given the need for anticoagulation, endovascular intervention in the form of thrombectomy or middle meningeal artery embolization may be a viable adjuvant to anticoagulation in select patients.